Aktivitas Antibakteri Ekstrak Etil Asetat Media Kultur Fungi Endofi t Nigrospora oryzae dari Rhizophora mucronata - Muhamad S. Fareza; Lingling T. Ayoesty; Siti R. Wargiyanti (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
The purpose of this study was to provide information on the antibacterial activity of ethyl acetate culture broth extract of endophytic fungi associated with Rhizophora mucronata. An isolated fungi was identifi ed as Nigrospora oryzae using microscopic and molecular analysis. Theantibacterial activity was carried out using micro dilution method to get MIC value. The ethyl acetate extract showed antibacterial activity with MIC value of 250 μg/mL against and Escherichia coli and 500 μg/mL against Staphylococcus aureus.